Genetic diversity of Central Javanese duck (Indonesia) based on Inter Simple Sequence Repeat markers - R. SUSANTI; AGUSTIN DIAN KARTIKASARI; FITRI ARUM SASI; DYKEN DWI ARLINDA (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Susanti R, Kartikasari AD, Sasi FA, Arlinda DD. 2022. Genetic diversity of Central Javanese duck (Indonesia) based on Inter Simple Sequence Repeat markers. Biodiversitas 23: 1807-1813. Genetic resources of local livestock need to be documented and conserved to prevent genetic erosion of the germplasm. This study aimed to determine the genetic diversity of domestic ducks (Anas platyrhynchos domesticus) in Central Java, Indonesia, based on Inter Simple Sequence Repeat (ISSR) markers. There were seven types of Central Javanese ducks used in this research. DNA was extracted from feathers samples. To give rise to ISSR profile of duck DNA, 5 different ISSR markers were used. Annealing temperature used in PCR was the result of the optimization. The ISSR-PCR results showed that all primers (100%) were polymorphic. From a total of five ISSR primers, resulted in 44 obvious bands in all duck samples, with 41 (91.78%) bands being polymorphic. The quantity of alleles was numerous from 7-14 polymorphic loci, the mean quantity of alleles according to locus was 8.8, and the average PIC score for the Central Javanese duck was 0.777. The relationship investigation showed that the Central Javanese local duck was clustered into two primary offshoots, one heading to Pengging duck breeds and another one consisting of all other Central Javanese local duck. The genetic diversity among Central Javanese local duck based on ISSR primer was high. The ISSR loci were polymorphic for Central Javanese duck and may be useful for study of genetic diversity and genome evolution of Central Javanese ducks in the future.